Великий адронний колайдер – досягнення та перспективи розвитку - Мічурін, І. Є. (ХНУРЕ, 2021)
The development of nuclear energy is impossible without understanding the fundamental aspects of nuclear physics. Particle physics is developing rapidly, so today the topic of experimental technology is relevant. The largest scientific project in this area was the creation of the Large Hadron Collider. It is important to understand the contribution of Ukrainian scientists and research institutions to the work of the Large Hadron Collider. It is also necessary to systematize the main achievements of research on the Large Hadron Collider. The study of the prospects for the development of research at the Large Hadron Collider will help to understand the directions of development of modern physics in the coming years
Keywords: адронний колайдер